Human cytomegalovirus glycoprotein B inhibits migration of breast cancer MDA‑MB‑231 cells and impairs TGF‑β/Smad2/3 expression - Yang, Rui; Liang, Jie; Xu, Guo-Xiong; Ding, Liu-Mei; Huang, Hong-Mei; Su, Qi-Zhu; Yan, Jing; Li, Yun-Chun (Oncology letters, 2018)
Breast cancer is a leading cause of cancer‑associated mortality in females worldwide and evidence suggests that human cytomegalovirus (HCMV) infection may be implicated in the progress of breast cancer. HCMV glycoprotein B (gB) is the most abundant envelope protein and serves an important role in host cell entry. The present study aimed to clarify the role of HCMV gB in breast cancer cells.
Gesehen am 29.04.2020